Sexually Dimorphic Neurotransmitter Release at the Neuromuscular Junction in Adult Caenorhabditis elegans - Yan, Zhenzhen; Cheng, Xinran; Li, Yuansong; Su, Zexiong; Zhou, Yiwei; Liu, Jie (Frontiers in Molecular Neuroscience, 2022)
Sexually dimorphic differentiation of sex-shared behaviors is observed across the animal world, but the underlying neurobiological mechanisms are not fully understood. Here we report sexual dimorphism in neurotransmitter release at the neuromuscular junctions (NMJs) of adult Caenorhabditis elegans. Studying worm locomotion confirms sex differences in spontaneous locomotion of adult animals, and quantitative fluorescence analysis shows that excitatory cholinergic synapses, but not inhibitory GABAergic synapses exhibit the adult-specific difference in synaptic vesicles between males and hermaphrodites. Electrophysiological recording from the NMJ of C. elegans not only reveals an enhanced neurotransmitter release but also demonstrates increased sensitivity of synaptic exocytosis to extracellular calcium concentration in adult males. Furthermore, the cholinergic synapses in adult males are characterized with weaker synaptic depression but faster vesicle replenishment than that in hermaphrodites. Interestingly, T-type calcium channels/CCA-1 play a male-specific role in acetylcholine release at the NMJs in adult animals. Taken together, our results demonstrate sexually dimorphic differentiation of synaptic mechanisms at the C. elegans NMJs, and thus provide a new mechanistic insight into how biological sex shapes animal behaviors through sex-shared neurons and circuits.